Falling mortality rates in Type 2 diabetes mellitus in the Wirral Peninsula: a longitudinal and retrospective cohort population-based study. Issue 1046 (17th August 2012) - Nwaneri, Chukwuemeka; Bowen-Jones, David; Cooper, Helen; Chikkaveerappa, Krishnamurthy; Afolabi, Banjo Adekunle
Abstract : Objectives: To determine the life expectancy and mortality rates in patients with type 2 diabetes mellitus when compared with the UK general population; to measure the years of life lost. Design: Longitudinal and retrospective cohort study. Setting: The Wirral Peninsula in the northwest of England. Participants: Total of 13 620 patients with type 2 diabetes mellitus on the Wirral Diabetes Register. Main Outcome measure: All-cause mortality, from 1 January 2000 to 31 December 2007. Results: Over the 8-year period of the study, there were a total of 16 692.5 person-years lived and 3888 deaths; 2041 (52.5%) males and 1847 (47.5%) females with corresponding mean ages at death of 75.6±10.3 years and 80.2±10.2 years, respectively. Although prevalence rates increased linearly (from 1.06% in 2000 to 4.39% in 2007) a decrease in mortality rates (from 117 to 46 per 1000 population) in both sexes was observed. This coincided with a progressive fall in cardiovascular risk factors in this population. A survival time curve of life lived until death showed that males had 8.0 years reduction in life span and females' life span was reduced by 9.6 years when compared with UK general population. In both sexes, life expectancy was reduced by between 2 and 11 years dependent on the age of diagnosis, with males showing a greater degree of reduction. Conclusion: Type 2 diabetes mellitus is associated with a significant reduction in life expectancy, more markedly in men, and in those diagnosed before age 70 years. However, annual mortality rates have fallen progressively in our population and may contribute to longer survival and life expectancy in future years.